Kosmologi Islam Pesisir Gunung Kidul (Mengungkap Corak, Praktek dan Ritual Keagamaan Asli Masyarakat Islam Pesisir ditinjau dari Nilai-Nilai Islam) - Agus Suprianto; Khoirul Anam (Mukaddimah: Jurnal Studi Islam, 2016)
Talks about Islamic and coastal communities nowadays being raged. It is based on the reality that religious complextion of coastal communities showedtheir own peculiarities as compared with a pattern of religious communities in another regions. Various kinds of ritual nuances of animism and dynamism are still carried out by coastal communities of Gunungkidul, such as sedekah laut, rasulan, nyadran, sedekahan, cincing guling, selametan, ledekan and ngalangi. In the fact, the majority of the communities over there are Muslim. Still exercise of the various kinds which nuances animistic and dynamistic makes the researches became passionate to do research. Two problems arise, why the Islamic community in the shouter coast of Gunungkidul still run a wide range of ritual and how it is according to Islam. By using sociological approach and maqasid shariah it can be concluded that there is still the exercise of various rituals such as the Islamisation process that is accommodative, the character of the Java community that mystical centric, their ignorance about the origin and meaning of the rituals and the lack of their knowledge of Islamic theology. In spirit, the various cultures and rituals are contract to Islam, but about the shape and the instrument has not to be conflict with Islam, both normative or historically. Indeed, various rituals and the instrument is contains of positive values such as the value of togetherness, helping each other, thanks favors, resigned and charity.